2020
DOI: 10.1038/s41598-020-61279-6
|View full text |Cite
|
Sign up to set email alerts
|

Duan-Nai-An, A Yeast Probiotic, Improves Intestinal Mucosa Integrity and Immune Function in Weaned Piglets

Abstract: Post-weaning diarrhea commonly occurs in piglets and results in significant economic loss to swine producers. non-antibiotic measures for managing post-weaning diarrhea are critically needed. Duannai-An, a probiotic produced from the yeast fermentation of egg whites, was previously shown to optimize intestinal flora and reduce the incidence of clinical diarrhea in weaning piglets. To study the effects of Duan-Nai-An on mucosal integrity and immunity in pig intestine, we examined the microstructure and ultrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
(35 reference statements)
2
19
0
2
Order By: Relevance
“…The starter feed is very crucial to a successful transition and the taste is important to piglets. They have to like what they are eating to continue to return to the feeder [15]. From our results of daily weight gain, daily food consumption, and feed conversion rate, additions of Totipro or/and PF1001 do not affect the daily food consumption significantly, while the daily weight gain is actually increased comparing to the control and antibiotic groups.…”
Section: Discussionmentioning
confidence: 69%
“…The starter feed is very crucial to a successful transition and the taste is important to piglets. They have to like what they are eating to continue to return to the feeder [15]. From our results of daily weight gain, daily food consumption, and feed conversion rate, additions of Totipro or/and PF1001 do not affect the daily food consumption significantly, while the daily weight gain is actually increased comparing to the control and antibiotic groups.…”
Section: Discussionmentioning
confidence: 69%
“…improve ADG and feed utilization of piglets (16)(17)(18). Yeast culture stimulated intestinal fermentation, increased the yield of volatile fatty acids and the products of bacterial fermentation, and provided some energy for pigs to improve nutrient utilization (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al [13] showed that yeast culture could signi cantly increase the feed intake of piglets. In addition, the researches on piglets and growing-nishing pigs showed that yeast culture could improve the daily gain and feed utilization rate of piglets [14][15][16] . It may be that yeast culture stimulated intestinal fermentation, increased the yield of volatile fatty acids and the end products of bacterial fermentation, and provided some energy for pigs to improve nutrient utilization [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%